2004
DOI: 10.1366/0003702042641380
|View full text |Cite
|
Sign up to set email alerts
|

C18-Modified Metal-Colloid Substrates for Surface-Enhanced Raman Detection of Trace-Level Polycyclic Aromatic Hydrocarbons in Aqueous Solution

Abstract: Metal colloids immobilized on a glass support substrate are modified with a self-assembled alkylsilane (C18) layer to promote adsorption of polycyclic aromatic hydrocarbons from aqueous solutions. Detection of these compounds from low concentration solutions is accomplished by using surface-enhanced Raman scattering (SERS). SERS spectra of pyrene adsorbed to C18-modified immobilized silver colloids are dominated by Raman bands that are not consistent with pyrene and indicate that pyrene undergoes a chemical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 48 publications
3
49
0
Order By: Relevance
“…The higher intensity of the SERS spectrum of bacteria was attributed to surface enhancement due to the presence of the silver colloid [27]. Such behavior has been reported in the literature for many other molecules and biomolecules [19,20,28,29].…”
Section: Sers Spectrasupporting
confidence: 69%
“…The higher intensity of the SERS spectrum of bacteria was attributed to surface enhancement due to the presence of the silver colloid [27]. Such behavior has been reported in the literature for many other molecules and biomolecules [19,20,28,29].…”
Section: Sers Spectrasupporting
confidence: 69%
“…Recently it has been demonstrated that PAH adsorption on nanostructured gold surfaces may cause their oxidative degradation. 16,17 When the applied potential is made more positive than + 0.9 V, Raman spectral changes indicate the electrochemical oxidation of adsorbed anthracene.…”
Section: Spectroelectrochemistrymentioning
confidence: 99%
“…Recently it has been demonstrated that PAH adsorption on nanostructured gold surfaces may cause their oxidative degradation. 16,17 When the applied potential is made more positive than + 0.9 V, Raman spectral changes indicate the electrochemical oxidation of adsorbed anthracene.New Raman bands, characteristic of oxidized species, are observed at 1032, 1600 and 1665 cm -1 . Changes are also seen in the high frequency region of the spectra, where characteristic vibrational modes of aromatic and aliphatic CH stretching appear.…”
mentioning
confidence: 99%
“…The frequency of the LSP resonance is tunable by the surface morphology. [10][11][12][13][14][15][16][17][18] A variety of substrates that support SERS are being explored by various groups. [1,4,19] Typically, an ideal SERS substrate for analytical applications should be robust, easy to prepare and use, provide a large enhancement of the interference-free Raman signal of the analyte, and present a high degree of reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…[15,28] This kind of approach for SERS-substrate preparation has recently attracted much attention. [11,[28][29][30][31][32][33][34] The self-assembled structures are fabricated by alternately dipping the initially flat surface into solutions containing a bifunctional cross-linker and the NPs. The resultant morphology can be tuned by the desired number of NP depositions, which tailors the substrate performance for SERS.…”
Section: Introductionmentioning
confidence: 99%